Paroxysmal Nocturnal Hemoglobinuria: Biology and Treatment - Carlos Bravo-Perez; Luca Guarnera; Nakisha D. Williams; Valeria Visconte (Medicina, 2023)
Paroxysmal nocturnal hemoglobinuria (PNH) is a nonmalignant clonal hematopoietic disorder characterized by the lack of glycosylphosphatidylinositol-anchored proteins (GPI-APs) as a consequence of somatic mutations in the phosphatidylinositol glycan anchor biosynthesis class A (PIGA) gene. Clinical manifestations of PNH are intravascular hemolysis, thrombophilia, and bone marrow failure. Treatment of PNH mainly relies on the use of complement-targeted therapy (C5 inhibitors), with the newest agents being explored against other factors involved in the complement cascade to alleviate unresolved intravascular hemolysis and extravascular hemolysis. This review summarizes the biology and current treatment strategies for PNH with the aim of reaching a general audience with an interest in hematologic disorders.